Imaging of Soft Tissue Tumors - Vanhoenacker, Filip M.; Parizel, Paul M.; Gielen, Jan L. (Springer International Publishing : Imprint: Springer, 2017)
This richly illustrated book, in an extensively revised new edition, provides a comprehensive survey of the role of medical imaging studies in the detection, staging, grading, tissue characterization, and post-treatment follow-up of soft tissue tumors. The indications for and relative merits of various imaging modalities are fully described, with particular emphasis on the role of advanced MRI techniques that can improve diagnostic accuracy and evaluation of treatment response. The most recent version of the WHO Classification of Soft Tissue Tumors is introduced, and individual chapters are devoted to imaging of each of the tumor groups in that classification as well as other soft tissue masses. Numerous new illustrations of both common and rare tumors are included, providing a rich pictorial database of soft tissue masses. In addition, imaging findings are correlated with clinical, epidemiologic, and histologic data. Imaging of Soft Tissue Tumors will be of value in daily practice not only for radiologists but also for orthopedic surgeons, oncologists, and pathologists.
Keywords: Medicine.; Radiology.; Oncology.; Orthopedics.; Pathology.; elektronické knihy; electronic books